Clearance flow patterns and pressure distribution of a pump-turbine: Measurement and simulation of a rotating disk flow - Hou, Xiaoxia; Liu, Herui; Cheng, Yongguang; Liu, Ke; Liu, Demin; Chen, Hongyu (Frontiers in Energy Research, 2022)
The clearance flow patterns and pressure distribution of pump-turbine determine the clearance axial hydraulic force, which significantly influences the balance of unit axial force. However, no detailed description of the flow and pressure characteristics exists because of the small size and complex structure of the clearance flow channel. In this study, we conducted a model test with PIV measurements and CFD simulation of a rotating disk flow that is a simplified model of the pump-turbine clearance flow. It was found that a typical Batchelor turbulence flow was formed in the clearance region, demonstrating a "core region + double boundary layers" distribution for the circumferential velocity along the clearance height direction; the core region rotates with a speed that is only around 41 to 42 percent of the rotating disk speed for all rotating conditions because of the centrifugal force caused by the rotation. Driven by the centrifugal force, the flow is radially outward around the rotating wall, while inward around the stationary wall in the meridian section, showing a secondary recirculation pattern. The pressure in the clearance region shows a circumferentially symmetric and radially quadratic distribution. Based on the liquid differential equilibrium equation and core region circumferential velocity, the pressure and clearance axial force can be expressed as a function of the clearance inlet pressure and the square of the runner rotating speed. These findings provide a basis for analyzing axial force imbalance problems of the pump-turbine unit.